METAPHORS THAT UNDERMINE HUMAN IDENTITY. - Gozzi Jr., Raymond (ETC: A Review of General Semantics)
Discusses the process discoverable in language about computers and about people that subtly undermines human dignity. Ways to prevent the metaphorical undermining of human identity; Description of the metaphorical use of human terms such as memory for computer capacity; Examples of terms with new definitions that clearly exhibits the externalization of human qualities onto machines.